An investigation to assess the impact of cost control on financial performance: ZETDC as a case study - Masocha, Walter Tafara (Midlands State University, 2017)
This study sought to investigate the impact of cost control on the financial performance of ZETDC. The population sample was drawn from 33 employees of the organisation and stratified random sampling was used to come up with a sample of 20 workers. The results showed that cost control enhances financial performance through better decision making. However, the company has been denied by regulatory authorities to implement some of its decisions necessitated by cost control. Cost control is also being affected negatively by delays by customers to pay their outstanding bills, heavy costs associated with implementation of cost control strategies and weak coordination between the management and workers. Poor cost control has adversely affected financial performance through failure to meet goals and objectives. The researcher recommends negotiations to be promoted between ZETDC and its regulatory authorities, cost-benefit-analysis to be done for every cost control strategy and interaction between management and workers should be promoted. Long outstanding debtors should submit payment plans which can result on further action being taken on them if they default agreed payment arrangements. Management should regularly review the entity’s internal controls to ensure compliance with cost control policies and procedures.